THE IMPLEMENTATION OF FLASHCARD IN IMPROVING CHILDREN’S INTEREST IN LEARNING ENGLISH AT KAMPUNG TANAMA - Arif Aminullah; Dian Eva Lestari (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2025)
This study explores the implementation of flashcards as a medium to enhance children’s interest in learning English in a community-based setting at Kampung Tanama, Fakfak, West Papua. Unlike formal school environments, the learning activities were conducted at the researcher’s home by inviting children from the neighborhood to participate in informal English lessons. The study employed a qualitative descriptive method, with observations and interviews as the main data collection techniques. The findings revealed that the use of colorful and interactive flashcards significantly increased children’s enthusiasm and participation. They became more active in repeating vocabulary, recognizing pictures, and engaging in simple English conversations. This research indicates that flashcards can be an effective tool in non-formal education to foster children’s motivation and interest in learning English.